ANALISA KALIBRASI ALAT ELECTROCARDIOGRAPH MENGGUNAKAN ELECTROCARDIOGRAPH SIMULATOR (PHANTOM ECG) - Martina Murniawati Gulo; Yulizham Yulizham (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2020)
An electrocardiograph is a device that can display a signal graphic showing the process of the heartbeat. From these signals it can be seen whether a person's heart rate is normal or not. The method used in this research is quantitative observation. Which aims to analyze the calibration of the Electrocardiograph (ECG) device using a simulator (Phantom ECG). And also aims to determine the results of the data obtained after observing the workflow of the tool. From the results of electrocardiograph testing at the Health Facility Security Center (BPFK) Medan, the results were obtained. Electrocardiograph testing at the paper speed set point 25 mm / sec 10 mm / mv obtained results of 25.18 +- 0.37 because it is within a tolerance value of +- 5%. At the paper speed set point of 50 mm / sec, 10 mm / sec, the result is 50.16 +- 0.37 because it is within a tolerance value of +- 5%. At the sensitivity setting point of 5 mm / mv, 25 mm / sec, the result is 5.24 +- 0.37 because it is within a tolerance value of +- 5%. At the sensitivity setting point of 10 mm / mv, 25 mm / sec, the result is 10.22 +- 0.37 because it is within a tolerance value of +- 5%. And at the sensitivity setting point of 20 mm / mv, 25 mm / sec, the result is 20.26 +- 0.36 because it is within a tolerance value of +- 5%.